2016
DOI: 10.3409/fb64_1.47
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Relationships between Endosymbiotic Green Algae of <I>Paramecium bursaria</I> Syngens Originating from Different Geographical Locations

Abstract: Paramecium bursaria (EHRENBERG 1831), a freshwater ciliate, typically harbors hundreds of green algal symbionts inside the cell. The aim of present study was the molecular identification of newly analyzed P. bursaria symbionts. The second aspect of the present survey was testing a hypothesis whether endosymbionts prefer the specified syngen of the host, and the specified geographical distribution. Ten strains of endosymbionts isolated from strains of P. bursaria originating from different geographical location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…In order to investigate the genetic basis of an emergent endosymbiotic system, we must develop experimentally tractable endosymbiotic model species [5][6][7] . Paramecium bursaria is a ciliate protist which harbours several hundred cells of the green algae, Chlorella spp., in a nascent facultative photo-endosymbiosis [8][9][10][11][12] . The algae provide sugar and oxygen derived from photosynthesis, in exchange for amino acids, CO2, divalent cations, and protection from viruses and predators 5,6,[13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to investigate the genetic basis of an emergent endosymbiotic system, we must develop experimentally tractable endosymbiotic model species [5][6][7] . Paramecium bursaria is a ciliate protist which harbours several hundred cells of the green algae, Chlorella spp., in a nascent facultative photo-endosymbiosis [8][9][10][11][12] . The algae provide sugar and oxygen derived from photosynthesis, in exchange for amino acids, CO2, divalent cations, and protection from viruses and predators 5,6,[13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…How do such relationships avoid over-exploitation by one partner that would ultimately lead the interaction to collapse? Partner switching is one option, however the result is typically a reduced pattern of co-evolution between symbiont and host that can inhibit the process of metabolic and genetic integration, stalling the evolution of stable interactions which are needed to produce new organelles [10][11][12][13][14] . Previous studies have suggested that when selfish behaviours arise, the evolution of enforcement to punish or suppress the exploitative partner can act to restore cooperation 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Identification of undirected 'RNAi collisions' in the P. bursaria -Chlorella system represents one such intermediary state, emergent in nature and untargeted, upon which sustained cellular interaction coupled with the potential for host-symbiont conflict could drive the selection of targeted RNA-RNA interactions. The reduced pattern of co-evolution between endosymbiont and host in the P. bursaria -Chlorella system, resulting from the potential for repeated partner switching by the host 11,34 , offers a possible explanation for why this mechanism has remained emergent.…”
Section: Discussionmentioning
confidence: 99%
“…After two days of incubation at 20 • C, the bacterized CM was ready for use. 3 : Friedrichsee, Saxony-Anhalt, Germany; 4 : Pond 'Pferdetränke', Oldenburg, Germany; 5 : Nymphensee, Rangsdorf, Germany; 6 : Loch Katrine, Scotland, United Kingdom; 7 : Saint Petersburg, pond in the park, Russia; 8 : Forest pond, Vyborg, Saint Petersburg region, Russia; 9 : Pond, Ardmoore, Oklahoma, USA; * Zagata et al, 2016 [60]; part. : partial.…”
Section: Strains and Cultivationmentioning
confidence: 99%